Mekanisme Afektif di Balik Impulsive Buying dalam Gim Mobile: Peran Perceived Enjoyment pada Mobile Legends: Bang Bang: Mekanisme Afektif di Balik Impulsive Buying dalam Gim Mobile: Peran Perceived Enjoyment pada Mobile Legends: Bang Bang - Foanto, Vasansya; Inkawidjaja, Griselda; Permana, Vincent; Muh Sa’ad; Monalisa (STIM-LPI Makassar, 2026)
The rapid expansion of mobile games with freemium business models has increased the need to understand the psychological mechanisms underlying impulsive buying behavior. This study examines the affective pathway driving impulsive in-game purchases by analyzing the effects of aesthetic quality, competitive drive, user experience, and perceived scarcity on impulsive buying, with perceived enjoyment as a mediating variable. Using a quantitative explanatory approach, data were collected from 216 active Mobile Legends: Bang Bang players in Indonesia who had previously made in-game purchases. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that aesthetic quality, competitive drive, user experience, and perceived scarcity have positive and significant effects on perceived enjoyment, with user experience and competitive drive emerging as the strongest predictors. Perceived enjoyment also has a strong positive effect on impulsive buying behavior, confirming its role as a key affective driver of spontaneous purchasing decisions. The study extends the Stimulus–Organism–Response framework and provides practical insights for sustainable mobile game monetization strategies.